Culture, consumerism & commercialisation: a history of Chinese proprietary medicine in twentieth-century Singapore - Teo, Ziqing (Nanyang Technological University, 2023)
The idea of dichotomising medical systems into traditional and modern is highly problematic as it often presents itself in the forms of institutional and social stigmas. Singapore, like many other countries, discriminated against Traditional Chinese Medicine (TCM) in favour for mainstream, western medicine. Often viewed as old, outdated, and therefore unreliable, the growth of the once-booming TCM industry became stagnated. Hence, through examining Chinese Proprietary Medicine (CPM), it challenges not just the validity of these stereotypes but also the preconceived notions of “modern”. As the most commercialised category of TCM, CPM is arguably the amalgamation of “East meets West”. As evident in its use of print media, CPM advertisements displayed highly innovative products reflective of trends then – not just in terms of illnesses and diseases, but also gender ideals and prevalent social issues. Concepts of “tradition” and “modern” were simply marketing tactics as the manufacturing processes continue to improve over the years. Street “medicine men” selling CPM were also more complex than simply frauds or quacks who sold counterfeit medicine. As cultural entrepreneurs, they were an intricate part of the medical network catering to the lower-class. Therefore, the existing, incomplete definitions of CPM and unstandardised classifications of CPM only further illustrate the prejudices held against CPM since the British rule. The failure to look pass this dichotomy therefore stands in the way of Singapore achieving true medical pluralism.